(untitled) (Research, Society and Development, 2020)
The tranquilization of acepromazine and the synergism resulting from its association with xylazine were evaluated. Seven pigs, SRD, healthy, male, aged 60 to 70 days and weighing on average 18.3 ± 2.7 kg were used. Compounds of two groups: group A - acepromazine 1%, 0.1 mg / kg, intramuscular; and 2% AX - xylazine group, 0.3 mg / kg, associated with 1% acepromazine, 0.1 mg / kg, in the same syringe. The following were evaluated: heart rate; systolic blood pressure; respiratory frequency; oxyhemoglobin saturation; body temperature and electrocardiogram. Sedation: absent, discrete or intense sedation. Muscle relaxation: absent, moderate or excellent. Measurement of the parameters: 0 and at 15, 30, 45, 60, 75, 90, 105 and 120 minutes after. The HR was higher in GA. There was no significant difference in f. SpO2 did not vary between groups or between moments. CT significantly reduced GAX. SBP did not vary in both groups. In the ECG, there was a change in the amplitude of the R wave. During the latency period and during the duration of sedation there was no significant difference between groups. In muscle relaxation GAX was higher in M75. Both protocols are safe and promote sedation in pigs, with synergism when using acepromazine associated with xylazine.